Farm : a push-and-pull adventure - Hill, Eric (London : Puffin Books, 2022)
Spot is helping Dad on the farm today - and there's lots to do! How many animals will they see? Curious young minds will love exploring the farmyard with Spot and Dad in this colourful, interactive board book. The sturdy novelty allows little hands to push, pull, slide, and play as they join in with feeding the chickens, cleaning the pigsty, and more. The gentle narrative introduces key farmyard vocabulary and animal noises, and is perfect for reading aloud.
Keywords: Animal - fiction; Board - book